The Modern Market for Soviet Movies: Social and Cultural Analysis of Market Positioning of DVD-Products - ПравдинаМария Александрова (Journal of Economic Sociology, 2010)
The paper is devoted to a socio-cultural analysis of the market for Soviet movies on DVD. The Soviet cinema is considered as a cultural object; and its positioning is connected with the production and distribution of cultural symbols representing meanings and values of the Soviet movies, on how the present and the Soviet past are related; on the role which the Soviet film production plays in the modern cultural context. The author brings up the following questions: how the Soviet movies are positioned in the DVD market? What cultural symbols are transmitted through this market positioning process? In which way do the properties of a movie conditioned by the institutional context of the Soviet film production define the distributors’ market strategies? The empirical data are collected from the covers of DVDs and descriptions, series, and collections of the Soviet movies presented on distributor-companies’ websites. The research covers 450 DVDs of the Soviet films.